The effects of corn gluten feed and corn dried distillers grains as a replacement for soybean meal on Boer type goat diets - Costigan, Samantha J.; Crane, Alison R.; Lattimer, James M.; Jones, Cassandra K. (My University, 2019)
No information regarding the use of corn dried distillers grains (DDGS) or corn gluten feed (CGF) is available in the 2007 Nutrient Requirements of Small Ruminants (NRC, 2007) This has caused a lack of knowledge about improving the nutritional requirements of the growing goat industry. The objective of this study was to evaluate the ability for CGF and DDGS to economically replace soybean meal (SBM) in Boer-type goat diets without affecting growth performance. This 35 d study included 75 Boer-type goats (26.9 ±0.2 kg) at approximately 70 d of age. Goats and treatments were randomly assigned to pens. There were 25 pens with 3 goats per pen and pen was the experimental unit. There were 5 isocaloric and isonitrogenous treatments for the study: 1) SBM; 2) 100% DDGS/0% CGF; 3) 66% DDGS/33% CGF; 4) 33% DDGS/66% CGF; 5) 0% DDGS/100% CGF. Goats and feeders were weighed weekly to calculate ADG, ADFI, and F:G. The data was analyzed using the GLIMMIX procedure of SAS (Cary, NC, V.4.4). There were no detected differences between treatments according to final BW, ADG, and F:G (P>0.05). Feeding goats a diet consisting of SBM increased (P=0.0008) feed costs/goat by approximately $0.04/kg of feed. This caused feed costs for goats being fed corn co-products to be lower than the feed costs for goats being fed SBM. Feeding a diet of corn co-product also increased (P=0.038) ADFI of the goats by approximately 0.045 kg/d, though there was no detected (P=0.444) difference in ADG. In conclusion, this study supports the use of CGF or DDGS as an economic replacement for SBM in Boer type goat diets.
Keywords: Spring 2019